Application of Biosensors in Diagnosis of Human Parvoviruses - Hosseini, Fatemeh; Zandi, Milad; Behboudi, Emad; Salmanzadeh, Shokrollah; Rasooli, Azadeh; Abbasi, Aida; Abbasi, Samaneh (Journal of Liaquat University of Medical & Health Sciences, 2023)
Human parvovirus B19 is a viral pathogen that causes acute and usually self-limiting disease. Because the B19 virus predicates erythroid progenitor cells, it can cause a transient aplastic crisis in immunocompromised individuals. This infection has been associated with nonimmunologic fetal hydrops during pregnancy; also, B19 can persist for months in immunocompromised individuals. In B19 infection, viremia with a high titer is observed for approximately one week. After that, a specific immune response is critical to control the infection. Although molecular and serologic tests commonly diagnose the B19 virus, laboratory diagnostic tests have limitations. For the detection of human parvovirus B19, an inexpensive, effective, and rapid biosensor may be considered as an alternative. Key Words: Human Parvovirus B19, Biosensor, Molecular and Serological Diagnosis.